Haploidentical Hematopoietic Stem Cell Transplant Complicated by Atypical Hemolytic Uremic Syndrome and Kidney Transplant From the Same Donor With No Immunosuppression but C5 Inhibition. Issue 2 (February 2019) - Ardissino, Gianluigi; Cresseri, Donata; Giglio, Fabio; Onida, Francesco; Iannuzzella, Francesco; Tel, Francesca; Giussani, Antenore; Messa, Piergiorgio; Longhi, Selena; Vincenti, Daniele; Tedeschi, Silvana; Cugno, Massimo; et al.
Abstract : Background: Atypical hemolytic uremic syndrome (aHUS) is life-threatening condition particularly when complicating allograft hematopoietic stem cell transplant (HSCT). In the past, the outcome was very poor with the majority of patients reaching end-stage renal disease or dying with little or no chances of kidney transplant (KTx) due to the high risk of relapse. The availability of C5 inhibition has opened up significant therapeutic opportunities and has improved the outcome particularly if complement dysregulation (CD) is the underlying pathogenetic mechanism. Methods: We describe a peculiar case of a girl with aHUS complicating HSCT and her subsequent successful KTx received from the same donor thus performed without immunosuppression but anti-C5 inhibition. Results: Soon after HSCT performed for acute lymphoblastic leukemia, the patient developed a TMA due to CD and reached end-stage renal disease. After 2 years on dialysis, the patient received a KTx from her father who was already the HSCT donor. Given the full chimerism, no immunosuppressive agent was prescribed except a short (2 days) course of steroids and eculizumab to prevent aHUS relapse. Nine months after the KTx, the patient is well with normal renal function, no immunosuppression and continues eculizumab prevention of aHUS (1 infusion every 21 days). Conclusions: All patients with transplant-associated thrombotic microangiopathy should be screened for the causes of CD. C5 inhibition with eculizumab is an important therapeutic resource to manage this complication. When KTx is necessary, immunosuppression can be safely withhold in case of same donor for both grafts and documented full chimerism. Abstract : This complex case describes a patient with B cell acute lymphoblastic leukemia treated with 2 hematopoietic stem cell transplants: the first, a matched unrelated, the second, a haplo-identical transplant from her father complicated by atypical-hemolytic uremic syndrome (aHUS) leading to end-stage renal disease followed by a kidney transplant without allo-immunosuppression, but reduced eculizumab to prevent aHUS caused by a putative autoantibody.